2004
DOI: 10.1152/jn.00186.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Currents in Subthalamic Nucleus Neurons From Nav1.6-Null Mice

Abstract: Do, Michael Tri H. and Bruce P. Bean. Sodium currents in subthalamic nucleus neurons from Na v 1.6-null mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 41 publications
1
76
0
Order By: Relevance
“…Based on the nearly complete elimination of resurgent currents in Purkinje neurons of Scn8a-null mice (Raman and Bean, 1999a,b), it had been thought that Na V 1.6 is unique in conducting resurgent sodium current, but recent studies of subthalamic neurons of Scn8a-null mice revealed that other sodium channels are also involved (Do and Bean, 2004). The reduction of resurgent sodium current in Purkinje neurons of Na V 1.1 HET and KO mice provides the first evidence for a role of a specific sodium channel subtype other than Na V 1.6 in generation of resurgent sodium currents in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the nearly complete elimination of resurgent currents in Purkinje neurons of Scn8a-null mice (Raman and Bean, 1999a,b), it had been thought that Na V 1.6 is unique in conducting resurgent sodium current, but recent studies of subthalamic neurons of Scn8a-null mice revealed that other sodium channels are also involved (Do and Bean, 2004). The reduction of resurgent sodium current in Purkinje neurons of Na V 1.1 HET and KO mice provides the first evidence for a role of a specific sodium channel subtype other than Na V 1.6 in generation of resurgent sodium currents in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Resurgent sodium current, a component of sodium current that flows transiently on repolarization of the cell, has been identified in cerebellar Purkinje neurons and other central neurons (Raman and Bean, 1997; Afshari et al, 2004;Do and Bean, 2004). Like the persistent sodium current, resurgent current has been implicated in promoting fast repetitive neuronal firing in these neurons Bean, 1997, 1999a; by accelerating depolarization toward threshold between action potentials (Raman and Bean, 1999a).…”
Section: Reduced Resurgent Sodium Current In Purkinje Neurons Of Het mentioning
confidence: 99%
“…Furthermore, a recent comparison of the same neurons and Purkinje neurons (46,47) suggests that slow inactivation or other putative sodium currents may contribute to the intriguing roles of resurgent and persistent currents. Since our study shows that Cn2 not only has sharp channel selectivity and binding stability for the Na v 1.6 isoform but also blocks firing in Purkinje neurons at appropriate concentrations, we propose using Cn2 as a leading compound for the study of Parkinson disease.…”
Section: Discussionmentioning
confidence: 99%
“…Li and Bennett (2003) demonstrated inward currents seen during slow ramp depolarizations that were insensitive to dihydropridines and blocked by TTX. It is known that some Na V subtypes mediate sodium currents with slower time constants of inactivation (Do and Bean, 2004), but the specific subtype of Na V channel which may underlie a Na-PIC is not yet clear. These currents are unlikely to be "persistent" or non-inactivating per se and are more likely to be slowly inactivating (Doand Bean, 2004).…”
Section: The Role Of Motoneuron Dendrites In Repetitive Firingmentioning
confidence: 99%